(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
As the internet has transformed the way we communicate, we need educational technology to transform the way students learn and teachers teach. One of the best examples of this type of transformation taking place is with the use of technology to teach students with disabilities. TTRS (Touch-type Read and Spell) is doing just that as their method uses typing letters (instead of handwriting them) to learn how to not only read and spell but also learn to touch-type. Their method relies on teaching correct finger position, repetition, along with audio and visual instruction.